Pengaruh lama fermentasi terhadap aktivitas antioksidan kombucha kunyit (Curcuma longa L.) sebagai minuman probiotik - Eri Nafisah; Linda Wige Ningrum; Rahmah Utami Budiandari; Lukman Hudi (Poltekkes Kemenkes Aceh, 2024)
AbstractBackground: Turmeric (Curcuma longa L.) is an herbal plant containing, the active compound curcumin, which has antioxidant and antibacterial properties, and its antioxidant content is equivalent to that of vitamin C and E. The active component of turmeric can be used as a probiotic drink, called kombucha. Kombucha is a tea fermented by bacteria and yeast which produce organic acids and antioxidants. Objectives: This study aims to formulate turmeric kombucha high antioxidant compound and analyze the antioxidant activity of tumeric kombucha.Methods: This research used one-factor RCBD, carried out starting in September 2023 four months in the Microbiology and Food Biotechnology Laboratory of the Bachelor of Food Technology Department, Universitas Muhammadiyah Sidoarjo. This research used fermentation time as factor (3,5,7,9,11,13,15) days and analysis of antioxidant activity was analyzed by DPPH method. The resulting data will be processed using ANOVA followed by the BNJ test at the 5% level.Results: The study showed that the time fermentation showed the antioxidant activity of turmeric kombucha was 57,58 ppm – 189,90 ppm. Increasing freephenol levels during fermentation will increases the antioxidant activity of kombucha.Conclusion: The fermentation time of turmeric kombucha affected its antioxidant activity.